The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1631/jzus.2007.b0070
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonic saline resuscitation maintains a more balanced profile of T-lymphocyte subpopulations in a rat model of hemorrhagic shock

Abstract: Abstract:Objective: To investigate the potential and early effect of hypertonic saline resuscitation on T-lymphocyte subpopulations in rats with hemorrhagic shock. Methods: A model of rat with severe hemorrhagic shock was established in 18 Sprague-Dawley (SD) rats. The rats were randomly divided into Sham group, HTS group (hypertonic saline resuscitation group) and NS group (normal saline resuscitation group). Each group contained 6 rats. The CD4 + and CD8 + subpopulations of T-lymphocytes in peripheral blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
(38 reference statements)
2
14
0
Order By: Relevance
“…All the rats suffered approximately 50% blood loss based on their body weight and survived in all the above-mentioned three phases. These results are consistent with our previous studies which reported that rats could survive acute blood loss to 50% 2007a;2007b). Fig.1 shows MAP changes of the rats in the three groups.…”
Section: Characteristics Of the Animal Modelsupporting
confidence: 92%
See 2 more Smart Citations
“…All the rats suffered approximately 50% blood loss based on their body weight and survived in all the above-mentioned three phases. These results are consistent with our previous studies which reported that rats could survive acute blood loss to 50% 2007a;2007b). Fig.1 shows MAP changes of the rats in the three groups.…”
Section: Characteristics Of the Animal Modelsupporting
confidence: 92%
“…Several laboratory studies have shown that ischemia-reperfusion injury can induce apoptosis (Zhao et al, 2003;Zhang et al, 2004;Wu et al, 2004). HTS resuscitation might prevent gut ischemiareperfusion injury by inducing overexpression of some cytoprotective proteins such as heme oxygenase-1 (HO-1), reducing the production of oxygenderived free radicals, regulating the inflammatory response, and decreasing oxidative stress (Ozgüç et al, 2003;Attuwaybi et al, 2004;Powers et al, 2005;Gonzalez et al, 2006;Lu et al, 2007b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe and controlled hemorrhagic shock was induced according to our previous studies (Lu et al, 2007;. Briefly, while under the mild anesthesia (40 mg/kg pentobarbital IP), acute hemorrhage was initiated (time=0 min) with four controlled blood withdrawals via the right carotid arterial cannula: 10 ml/kg per 5 min for the first two withdrawals, then 5 ml/kg per 5 min for the second two, to yield a total hemorrhage volume of 30 ml/kg.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…In addition, HTS resuscitation suppresses the release of proinflammatory cytokines (Isayama et al, 2012), and thus might improve immunosuppressive reactions after hemorrhagic shock. Indeed, our previous studies indicate that HTS alleviates immune disorders and limits tissue injury after hemorrhagic shock (Lu et al, 2007;.…”
Section: Introductionmentioning
confidence: 96%